The love of my life : a novel - Walsh, Rosie (Pamela Dorman Books/Viking, 2022)
"From the New York Times bestselling author of Ghosted comes a love story wrapped in a mystery: an up-all-night page-turner with a dark secret at its core I have held you at night for ten years and I didn't even know your name. We have a child together. A dog, a house. Who are you? Emma loves her husband Leo and their young daughter Ruby: she'd do anything for them. But almost everything she's told them about herself is a lie. And she might just have got away with it, if it weren't for her husband's job. Leo is an obituary writer; Emma a well-known marine biologist. When she suffers a serious illness, Leo copes by doing what he knows best - researching and writing about his wife's life. But as he starts to unravel the truth, he discovers the woman he loves doesn't really exist. Even her name isn't real. When the very darkest moments of Emma's past finally emerge, she must somehow prove to Leo that she really is the woman he always thought she was . . . But first, she must tell him about the love of her other life."--